Mariposa Festival 1975 - N/A (1975)
Image of First Nations woman selling beadwork and mocassins. We acknowledge the financial support of the Department of Canadian Heritage through the Canadian Culture Online Program. | Nous tenons à souligner le soutien financier du ministère du Patrimoine canadien par le biais du Programme de culture canadienne en ligne.